Z Fredrą dyliżansem i koleją - Poklewska, Krystyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The present paper is devoted to two little-known comedies by Aleksander Fredro: The Stagecoach (1827) and From Przemyśl to Przeszowa (1867). The interesting thing is that the main construction principle of both stories is the time span of the journey taken by the protagonists, defining the beginning and end of their adventures. The time spent together by the characters, travelling by stagecoach in one of the comedies and by train in the other, unites a casual group of persons, which results in creating new relationships. The common journey from Płock to Toruń and from Przemyśl to the Czech town of Przerów (“Przeszowa”) provides a framework for the storyline. Both the comedies are examples of travel writing, combining various theatrical conventions and traditions: farce, bourgeois comedy, drama, and serious comedy. In The Stagecoach, comedy characters of different origin (from burlesque to tragedy) meet and in From Przemyśl to Przeszowa, a number of farcical twists and situations are followed by a happy ending of a family drama. Both the comedies are set in the rich reality of nineteenth-century travels: from the appearance of different railway station buildings and the menu in each successive restaurant to animosities between particular passengers resulting from the discomfort of travelling together.